Understanding Policy Domains their Salient Forces and Organisational Challenges. - Chirawu, Tapera O. (University of Namibia Press, 2012)
Understanding Policy Domains, their Salient Forces, and Organisational Challenges examines the complexity of policy making processes within the context of human action arising from culture, life necessities, and politics. It provides an understanding of human, environmental and institutional behaviour, and identifies the policy factors that underline the success or failure of governments and institutions. This book provides policy-makers, practitioners and other researchers in the field with a clear understanding of the process of policy-making and who is responsible for what. It sets the tone.